COVID-19, innovative firms and resilience - Battisti, Michele; Belloc, Filippo; Del Gatto, Massimo (World Intellectual Property Organization, 2023)
This paper explores the empirical association between patents and various indicators of firm resilience during the COVID-19 pandemic with worldwide firm-level data from manufacturing industries. The study shows that patent-intensive firms have a reduced probability of exit, in particular if they are larger and if engaging with complementary investments in R&D and other intangibles. Additional estimates show that firm productivity has been an important transmission channel. Taken together, the results presented in the paper offer evidence-based findings pointing to patents as an important potential factor contributing to firm resilience during the COVID-19 pandemic. Policy insights are discussed.
Keywords: Patents.; Manufacturing industries.; COVID-19 (Disease)